IMPLEMENTASI SMART CONTRACT UNTUK PENCATATAN RANTAI PASOK BATERAI KENDARAAN LISTRIK KONVERSI - Agung, Anak Agung Gde; Yuniar, Irna; Kastaman, Kastaman (Jurnal Abdimas Bina Bangsa, 2024)
After more than 200 years of dependence on refined petroleum fuels, currently countries in the world are starting to switch to battery-based electric vehicles (EV). Apart from being considered cheaper in operational costs, EV technology is considered mature enough for mass use. The battery is one of the core components for EVs, which contributes to around 40% of the production costs of the EV itself. For this reason, EV producing countries and battery manufacturing material providers are competing to secure the material supply chain and battery processing installations. Another reason for the need to secure the battery supply chain is that the materials used to make EVs come from mining materials which have the potential to pollute the environment and be dangerous to health. For this reason, a recording and tracking mechanism is needed in the battery supply chain, starting from raw materials to reuse/post usage. Blockchain through smart contracts can handle this problem. Smart contract applications running on blockchain have immutable and traceable properties, two properties that are critical points in the supply chain. Blockchain also has transparent and secure properties, so that even though only defined parties can interact, supply chain data can be seen by users. The solution and output target for this Community Service activity is to adapt the smart contract that was created in previous research with the partner's business process, and test the performance of the smart contract directly. By implementing this smart contract, it is hoped that partners will have more competitive advantage in the electric motorbike conversion workshop ecosystem